Alternative Theories of Monetary Policy - Filipovski, Vladimir (University of Belgrade, Faculty of Economics and Business, Belgrade, Serbia, 2022)
The outcomes of quantitative easing (QE) programs post-Great Recession have challenged the conventional theory of monetary policy. Alternative theories have offered their explanations for why expansionary policies did not produce inflation. In this context, this paper will apply a theoretical analysis to two alternative views of QE programs and their policy implications: the Fiscal Theory of Price Level (FTPL) and the Market Monetarism (MM). FTPL offers an explanation based on the intertemporal-government-budget equation in which the price level is a relative price of nominal government debt in terms of real resources government can extract via taxation (present value of expected budget surpluses). FTPL claims that QE basically substitutes one type of government liabilities for another type of government liabilities – (interest bearing) reserve money for government bonds, so the overall effect of the program may not be inflationary. The Market Monetarism (MM) is another alternative view to monetary policy. Although based on the quantity theory-of-money equation, MM explains why the FED policy during the Great Recession (particularly during 2008 and 2009) was in fact tight (relative to increased real demand for money). According to MM, the increase in base money due to QE programs was in fact offset by a decrease in money multiplier and a fall in velocity of money. But the key policy implication of the MM is that inflation targeting should be replaced by nominal GDP targeting. In this framework, monetary aggregates should be replaced by asset market prices, as indicators for the monetary policy stance and as policy targets. The paper will include assessment of the implications of the two theories for the issue of coordination between monetary policy and fiscal policy.
Keywords: MONETARY POLICY, FISCAL THEORY OF PRICE LEVEL, MARKET MONETARISM, QUANTITATIVE EASING.